Three-Dimensional Hydrodynamic and CFD Modeling of a Tidal Barrage Power Plant without Sluicing in Buenaventura, Colombia - Daniel Parrado; Juan Gabriel Rueda-Bayona (Infrastructures, 2024)
Recent research revealed the potential of tidal energy in the central coastal region of the Colombian Pacific. Buenaventura City, located in the Valle del Cauca department in Colombia, has an important opportunity to develop tidal power technologies near its marine coastal areas. This research implemented a 3D hydrodynamic model for simulating the hydrodynamics of the Buenaventura Bay to provide data as input for evaluating the hydraulics of a tidal barrage without sluicing through CFD modeling. According to the results, the velocities across the gates during Syzygy (April 2021) showed impressive velocities between 9 and 11 m/s, which suggest a high possibility of producing electricity through tidal turbines. The mean behavior of velocities in the gates pointed to values of 3 and 5 m/s in most of the cases. The results during the Stoa condition were interesting because flow velocities higher than 1 m/s were not expected. This is promising because the plant might produce electricity even during the Stoa condition. For the first time, the results of this research suggest that there exists a high possibility of implementing tidal barrage plants in Buenaventura City, Colombia.